Accounting for the Rise of Health Spending and Longevity - Raquel Fonseca; Pierre-Carl Michaud; Arie Kapteyn; Titus Galama (Institute for the Study of Labor (IZA), 2013)
We estimate a stochastic life-cycle model of endogenous health spending, asset accumulation and retirement to investigate the causes behind the increase in health spending and longevity in the U.S. over the period 1965-2005. We estimate that technological change and the increase in the generosity of health insurance on their own may explain 36% of the rise in health spending (technology 30% and insurance 6%), while income explains only 4% and other health trends 0.5%. By simultaneously occurring over this period, these changes may have led to complementarity effects which we find to explain an additional 57% increase in health spending. The estimates suggest that the elasticity of health spending with respect to changes in both income and insurance is larger with co-occurring improvements in technology. Technological change, taking the form of increased health care productivity at an annual rate of 1.3%, explains almost all of the rise in life expectancy at age 25 over this period, while changes in insurance and income together explain less than 10%. Welfare gains are substantial and most of the gain appears to be due to technological change.
Keywords: I10; I38; J26; 330; health spending; longevity; life-cycle models; technological change